2013
DOI: 10.1002/jgrd.50358
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intercalibration methods for satellite microwave humidity sounders

Abstract: [1] Three methods for intercalibrating humidity sounding channels are compared to assess their merits and demerits. The methods use the following: (1) natural targets (Antarctica and tropical oceans), (2) zonal average brightness temperatures, and (3) simultaneous nadir overpasses (SNOs). Advanced Microwave Sounding Unit-B instruments onboard the polar-orbiting NOAA 15 and NOAA 16 satellites are used as examples. Antarctica is shown to be useful for identifying some of the instrument problems but less promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Ways to compare measurements by different satellite instruments include the simultaneous nadir overpasses technique (limiting the comparisons to the highest latitudes, John et al, 2012) and the use of "natural targets" that have very little variability or the averaging over a lot of scenes (John et al, 2013a). Another technique is the double difference technique that uses NWP fields input to a RTM as a transfer function between two radiometers that have few common overpasses.…”
Section: Intercomparison Of Instrumentsmentioning
confidence: 99%
“…Ways to compare measurements by different satellite instruments include the simultaneous nadir overpasses technique (limiting the comparisons to the highest latitudes, John et al, 2012) and the use of "natural targets" that have very little variability or the averaging over a lot of scenes (John et al, 2013a). Another technique is the double difference technique that uses NWP fields input to a RTM as a transfer function between two radiometers that have few common overpasses.…”
Section: Intercomparison Of Instrumentsmentioning
confidence: 99%
“…Far from nadir, channels sounding deep into the troposphere, located on the wings of the 183.31 GHz line, might be more affected by antenna issues than higher peaking channels, located in the center of the line, due to radiation measured by the side lobes. Such asymmetries were found for AMSU-B and MHS (Buehler et al, 2005b;John et al, 2013b), but so far the monitoring of SAPHIR has not shown any scan asymmetry. For ATMS, comparisons of temperature data records (TDRs, calibrated antenna temperatures) and sensor data records (SDRs, BT after further applying beam efficiency and scan-position-dependent bias corrections) for the 183 GHz channels show the same behavior meaning that the TDR to SRD conversion is not responsible for the bias, although it seems to introduce some dependence on the viewing angle that warrants further investigation.…”
Section: Scan Asymmetrymentioning
confidence: 85%
“…The amplitudes a 1 and a 2 are 0.06% RH and 0.11% RH respectively. However, combining the ascending and descending orbits to deduce the inter-satellite biases can almost completely eliminate the 24 h amplitude (a 1 ) of the diurnal cycle with a very small remnant diurnal amplitude (a 2 ) [36].…”
Section: Diurnal Cycle From Microwave Measurementsmentioning
confidence: 99%